POLRI DI ERA DEMOKRASI : Dinamika Pemikiran Internal - Yanuarti, Sri (Pusat Penelitian Politik, 2011)
Police reform is an integralpart ofholistic security sector reform SSR which aims to create goodgovernancein the security sector and to create a secure and orderly environment Thus in accordance with the principles ofdemocracy police reform should have been directed to build a civilian policing character based on democraticnorms openness and accountability Although police reform already been done since more than a decade ago itsimplementation has not been optimal Thepresence ofpolice as an institution and its members still have a negativeimage in the eyes ofpeople because ofthe actions ofcertain person ofpolice personnel The study is to describe1 How does the present shift ofIndonesian police from the era ofauthoritarianism to era of democracy 2 whatfactors that encourage and inhibit the process ofpolice reform what kind ofconstraints that itface as well as theimpact ofthe constraints 3 How do internal dynamics which occurs in the thought ofpolice reform itself